2014
DOI: 10.1007/s11912-014-0411-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dietary Supplements in Oncology

Abstract: The use of dietary supplements among patients affected by cancer is extensive, with an estimated 20-90 % of patients using these products. Their use of these products is often not shared with the treating physician. This is because patients perceive or believe that their physicians are indifferent or negative toward the use of dietary supplements. As a result, patients may obtain information about dietary supplements from unreliable sources, exposing themselves to unnecessary risks. Since there are limited sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…Since a clear, official definition of dietary supplements does not currently exist in Japan, many dietary supplements claim to treat specific diseases, especially cancer, even though such claims are illegal. Previous studies reported that between 20% and 90% of cancer patients used dietary supplements as complementary and alternative medicines, not only in Japan [ 20 ], but also in other countries [ 21 , 22 , 23 , 24 ]. Furthermore, since dietary supplements are available as capsules or tablets, they have the appearance of medicines and, thus, are often considered to be as effective as medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Since a clear, official definition of dietary supplements does not currently exist in Japan, many dietary supplements claim to treat specific diseases, especially cancer, even though such claims are illegal. Previous studies reported that between 20% and 90% of cancer patients used dietary supplements as complementary and alternative medicines, not only in Japan [ 20 ], but also in other countries [ 21 , 22 , 23 , 24 ]. Furthermore, since dietary supplements are available as capsules or tablets, they have the appearance of medicines and, thus, are often considered to be as effective as medicines.…”
Section: Introductionmentioning
confidence: 99%
“…According to different studies, cancer patients use CAM to sustain physical well-being by reducing symptoms of their disease and alleviating side effects of conventional treatments to actively participate in and contribute to the cure of their cancer by supporting their body and immune system, to prevent later recurrence of the disease, or even to control the growth of abnormal cells and cure their cancer [ 46 , 47 , 90 ]. Considering a possible dissatisfaction with conventional therapies, the decision for alternative treatments—which are misperceived as safe therapies with few side effects—also reflects a desire for less toxic treatments [ 28 , 33 , 91 ].…”
Section: Systematic Review On the Self-administered Use Of Cam Supple...mentioning
confidence: 99%
“…Although our proposed approach has many potential advantages, there are challenges to conducting validating clinical studies. First, there is a shortage of funding for this type of initiative due to lack of patentability, manufacturing difficulties, contamination, and lack of product consistency [82] . Second, the use of NHPs among cancer patients is quite common.…”
Section: Tissue Invasion and Metastasismentioning
confidence: 99%